2017
DOI: 10.1016/j.bbamcr.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Tubular lipid binding proteins (TULIPs) growing everywhere

Abstract: Tubular lipid binding proteins (TULIPs) have become a focus of interest in the cell biology of lipid signalling, lipid traffic and membrane contact sites. Each tubular domain has an internal pocket with a hydrophobic lining that can bind a hydrophobic molecule such as a lipid. This allows TULIP proteins to carry lipids through the aqueous phase. TULIP domains were first found in a large family of extracellular proteins related to the bacterial permeability-inducing protein (BPI) and cholesterol ester transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 109 publications
(184 reference statements)
0
51
0
Order By: Relevance
“…AcrIIC2 adopts an a 1 b 1-6 a 2 fold, with the C-terminal long a helix inserted into the half-barrel structure formed by the six b strands (Figure 2A). A Dali server search revealed that AcrIIC2 monomer shares some structural similarity with the tubular lipidbinding proteins ( Figure S2F) (Wong and Levine, 2017;Jeong et al, 2017); however, the AcrIIC2 dimer represents a novel fold with no reported homologous structures. The dimerization of AcrIIC2 is mediated by a 1 , b 1 , b 2 , b 3 , and adjacent loops of both monomers through the formation of a compact hydrophobic core (Figures 2A and 2B).…”
Section: Acriic2 Dimerization Is Critical For Nmecas9 Inhibitionmentioning
confidence: 99%
“…AcrIIC2 adopts an a 1 b 1-6 a 2 fold, with the C-terminal long a helix inserted into the half-barrel structure formed by the six b strands (Figure 2A). A Dali server search revealed that AcrIIC2 monomer shares some structural similarity with the tubular lipidbinding proteins ( Figure S2F) (Wong and Levine, 2017;Jeong et al, 2017); however, the AcrIIC2 dimer represents a novel fold with no reported homologous structures. The dimerization of AcrIIC2 is mediated by a 1 , b 1 , b 2 , b 3 , and adjacent loops of both monomers through the formation of a compact hydrophobic core (Figures 2A and 2B).…”
Section: Acriic2 Dimerization Is Critical For Nmecas9 Inhibitionmentioning
confidence: 99%
“…One class of lipid-transport modules found in intracellular proteins that function at membrane contact sites are SMP (synaptotagmin-like, mitochondrial and lipid-binding protein) domains (8)(9)(10)(11). These domains represent a branch within the superfamily of TULIP (tubular lipid-binding) domains that comprise members found both in intracellular and extracellular proteins (12).…”
mentioning
confidence: 99%
“…Evidence for additional LTPs that operate at ER‐PM contact sites and possess functions related to the PtdIns cycle have recently emerged; including complex signaling‐related roles for the relatively promiscuous TUbular LIPid‐binding (TULIP) family of LTPs, which possesses synaptotagmin‐like mitochondrial lipid‐binding protein (SMP) LTDs . While the LTDs from both families of PITPs appear to function as monomeric shuttles for a restricted group of lipid isomers, SMP domains promiscuously transfer glycerophospholipids, showing little headgroup specificity, and are capable of forming dimeric complexes or perhaps even larger macromolecular assemblies .…”
Section: Additional Lipid Transfer Proteins With Functions At Er‐pm Cmentioning
confidence: 99%